The Role of Customer Relationship and Innovation Readiness on Marketing Behavior: The Mediating Effect of Customer Management - Dedi Iskamto; Jenita Jenita; Ayub Ayub; Fasya Hauna; Ahmad Zainudin Awang (International Journal of Entrepreneurship and Business Management, 2026)
This study examines the influence of Customer Relationship (CR) and Innovation Readiness (IR) on Marketing Behavior (MB) through the mediating role of Customer Management (CM). Using a quantitative approach with Partial Least Square – Structural Equation Modeling (PLS-SEM), data were collected from 353 respondents via a structured Likert-scale survey instrument. The measurement model demonstrates satisfactory reliability (Cronbach's α ≥ 0.72; Composite Reliability ≥ 0.83) and convergent validity (AVE ≥ 0.50). Hypothesis testing results indicate that Customer Relationship significantly influences Customer Management (β = 0.468, t = 10.699, p < 0.001), Innovation Readiness significantly influences Customer Management (β = 0.287, t = 6.421, p < 0.001), and Customer Management exerts the strongest effect on Marketing Behavior (β = 0.855, t = 23.143, p < 0.001). The R² values of 0.622 and 0.604 indicate moderate explanatory power for CM and MB respectively. These findings contribute to the growing body of literature on marketing strategy and digital transformation in service-oriented firms, highlighting customer management as a critical conduit between relational capabilities and behavioral marketing outcomes.